2011
DOI: 10.1152/ajpendo.00534.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet-induced obesity and metabolic syndrome on skeletal muscles of Ossabaw miniature swine

Abstract: TY. Effect of diet-induced obesity and metabolic syndrome on skeletal muscles of Ossabaw miniature swine. Am J Physiol Endocrinol Metab 300: E848 -E857, 2011. First published February 8, 2011 doi:10.1152/ajpendo.00534.2010.-Ossabaw swine fed excess kilocalorie diet develop metabolic syndrome (MS) characterized by obesity, hypertension, insulin resistance, and glucose intolerance with/ without dyslipidemia. The purpose of this study was to test the hypothesis that MS would have a detrimental effect on skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Few reports exist whereby this phenomenon even is evident in domesticated (meat) animals, but three studies are available evaluating this event in pigs. [133][134][135] In a study utilizing pigs of different body composition, Reiter et al demonstrated that genetic preference for leanness resulted in lower genetic markers for variables of adiposity and lipid metabolism within adipose tissue over pigs of more conventional body composition. 134 However, select skeletal muscle markers for oxidative metabolism of lipids were higher in the leaner pig group; suggesting that intramyocellular lipid is processed more rapidly in lean-type pigs over conventional pigs of similar age and such metabolism is heightened by application of commercially available b-adrenergic agents.…”
Section: Intramyocellular Lipid Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports exist whereby this phenomenon even is evident in domesticated (meat) animals, but three studies are available evaluating this event in pigs. [133][134][135] In a study utilizing pigs of different body composition, Reiter et al demonstrated that genetic preference for leanness resulted in lower genetic markers for variables of adiposity and lipid metabolism within adipose tissue over pigs of more conventional body composition. 134 However, select skeletal muscle markers for oxidative metabolism of lipids were higher in the leaner pig group; suggesting that intramyocellular lipid is processed more rapidly in lean-type pigs over conventional pigs of similar age and such metabolism is heightened by application of commercially available b-adrenergic agents.…”
Section: Intramyocellular Lipid Dynamicsmentioning
confidence: 99%
“…134 Utilizing genetically small pigs, which are isolated from other breeds, it was shown that diets to mimic dyslipidemic metabolic syndrome resulted in greater accumulation of intramyocellular lipid, but did not result in greater overall numbers of lipid droplets in pigs. 133 Moreover, skeletal muscle contractile proteins appear altered when excess lipid was incorporated Abbreviations: BF, biceps femoris; LD, longissimus dorsi; ST, semitendinosus; RF, rectus femoris; FCN, fat cell number; FCS, fat cell size.…”
Section: Intramyocellular Lipid Dynamicsmentioning
confidence: 99%
“…Val-Laillet et al, 2010a, 2010band 2010c. Thus, conventional pigs and minipigs are often used as models of high-fat and/or high-carbohydrate diet-induced obesity (Val-Laillet et al, 2010a, 2010b, 2010c, Clark et al, 2011), diabetes (Bellinger et al, 2006Liu et al, 2007) or atherosclerosis (Xi et al, 2004). With regard to hormonal regulation of feeding behaviour, pigs and humans share some taste receptors and hormones that are involved in appetite/satiety regulation.…”
Section: Have Demonstrated Thatmentioning
confidence: 99%
“…Gö ttingen minipigs also have a high propensity The pig model in human nutrition (Gandarillas and Bas, 2009) Differences in the relative absorptive surface areas of the GIT (e.g. faster nutrient absorption in humans than in rats; DeSesso and Jacobson, 2001) Ability to develop human diseases Obesity (Val-Laillet et al, 2010a, 2010band 2010cClark et al, 2011), diabetes (Bellinger et al, 2006Liu et al, 2007), atherosclerosis (Xi et al, 2004;Miyoshi et al, 2010).…”
Section: Have Demonstrated Thatmentioning
confidence: 99%
See 1 more Smart Citation